Synthesis of biodegradable polymer-mesoporous silica composite microspheres for DNA prime-protein boost vaccination - Ho, J.; Huang, Y.; Danquah, Michael; Wang, H.; Forde, G. (Elsevier Science, 2010)
DNA vaccines or proteins are capable of inducing specific immunity; however, the translation to the clinic has generally been problematic, primarily due to the reduced magnitude of immune response and poor pharmacokinetics. Herein we demonstrate a composite microsphere formulation, composed of mesoporous silica spheres (MPS) and poly(d,l-lactide-co-glycolide) (PLGA), enables the controlled delivery of a prime-boost vaccine via the encapsulation of plasmid DNA (pDNA) and protein in different compartments. Method with modified dual-concentric-feeding needles attached to a 40 kHz ultrasonic atomizer was studied. These needles focus the flow of two different solutions, which passed through the ultrasonic atomizer. The process synthesis parameters, which are important to the scale-up of composite microspheres, were also studied. These parameters include polymer concentration, feed flowrate, and volumetric ratio of polymer and pDNA-PEI/MPS-BSA. This fabrication technique produced composite microspheres with mean D[4,3] ranging from 6 to 34 µm, depending upon the microsphere preparation. The resultant physical morphology of composite microspheres was largely influenced by the volumetric ratio of pDNA-PEI/MPS-BSA to polymer, and this was due to the precipitation of MPS at the surface of the microspheres. The encapsulation efficiencies were predominantly in the range of 93-98% for pDNA and 46-68% for MPS. In the in vitro studies, the pDNA and protein showed different release kinetics in a 40 day time frame. The dual-concentric-feeding in ultrasonic atomization was shown to have excellent reproducibility. It was concluded that this fabrication technique is an effective method to prepare formulations containing a heterologous prime-boost vaccine in a single delivery system. © 2010 Elsevier B.V. All rights reserved.